2015
DOI: 10.5020/18061230.2015.p351
|View full text |Cite
|
Sign up to set email alerts
|

Análise do estado de funcionalidade de idosos residentes em unidades de longa permanência

Abstract: RESUMOObjetivo: Analisar o estado de funcionalidade de idosos residentes em unidades de longa permanência. Métodos: Estudo descritivo-exploratório desenvolvido em duas instituições de longa permanência para idosos (ILPI) no município de Fortaleza-CE, no período de novembro de 2012 a julho de 2013. Os instrumentos utilizados foram: 1) formulário sociodemográfico, 2) Medida de Independência Funcional (MIF) e 3) Classificação Internacional de Funcionalidade (CIF). Os dados foram analisados de maneira descritiva a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
1
2
1
2
Order By: Relevance
“…4±28.6 (Calero-García, Calero, Navarro, Ortega, & Campos, 2016). These data differ from those of other studies, which show means of 121.6 points for institutionalized senior patients, and 69.35 for elderly individuals who went home after fractures, which may reinforce the fact that hospitalization reduces the elderly's functionality significantly (Silva, Rojas, & Marzuca-Nassr, 2015;Josino, Costa, Vasconcelos, Domiciano, & Brasileiro, 2015).…”
Section: Discussioncontrasting
confidence: 97%
“…4±28.6 (Calero-García, Calero, Navarro, Ortega, & Campos, 2016). These data differ from those of other studies, which show means of 121.6 points for institutionalized senior patients, and 69.35 for elderly individuals who went home after fractures, which may reinforce the fact that hospitalization reduces the elderly's functionality significantly (Silva, Rojas, & Marzuca-Nassr, 2015;Josino, Costa, Vasconcelos, Domiciano, & Brasileiro, 2015).…”
Section: Discussioncontrasting
confidence: 97%
“…It is known that functional capacity tends to decrease over the years, especially over 70 years of age. We observed that there were negative correlations between age and functional performance, where for each increase in years lived, the results of performance tests were worse, corroborating studies already carried out [26][27][28].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the influence of pain on physical performance and the fear of falling in older residents in LSIs was observed, showing that the higher the pain scores, the worse the results of gait speed, balance, time to sit and stand and greater is the fear of falling. The presence of these results can be explained by the characteristics of institutionalized older people [26], in which the majority presented as low education, female, with advanced ages and without a spouse (widowed/single), which are risk factors for the development of disabilities [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O uso desse processo metodológico não é obrigatório, o que contribui para que estudos demonstrem outras metodologias de ligação, como o consenso e o nível de concordância entre avaliadores 61,62,78 . Porém, a não explicitação do método de ligação limita a reprodutibilidade do estudo, o que ocorreu nos estudos de Nickel et al 44 , Carvalho et al 34 , Josino et al 40 , Philbois et al 56 , Gomes et al 57 e Moura et al 54 . Dois estudos de revisão sobre a aplicação da CIF no Brasil identificaram Neurologia, Ortopedia e Reumatologia como os contextos mais frequentes 12,14 assim como os achados do presente estudo.…”
Section: Quadro 2 Continuaçãounclassified